Anti-tumor effects of recombinant human cyclophilin A combined with immune checkpoint inhibitors in the experimental model of melanoma B16 in vivo - A. A. Kalinina; D. B. Kazansky; L. M. Khromykh (Успехи молекулярной онкологии)
Introduction. Immune checkpoint inhibitors have an exceptional position in cancer immunotherapy. Currently, anti-CTLA-4 (cytotoxic T-lymphocyte-associated protein 4) and anti-PD-1/PD-L1 (PD-1 – programmed cell death 1, PD-L1 – programmed death 1 ligand 1) therapies are most widely applied in clinical practice. Still, immune checkpoint inhibitors therapy is not always successful, and multiple studies have indicated that it should be combined with other immunotherapeutic strategies, including cytokines. Secreted cyclophilin A (CypA) could be of particular interest in this respect. Previously, we showed that recombinant human CypA (rhCypA) had pleiotropic immunostimulatory activity and anti-tumor effects. Studies of rhCypA as an anti-cancer factor pointed to its potential use in cancer chemoimmunotherapy and combination immunotherapy.Aim. To evaluate anti-tumor effects of combined immunotherapy using rhCypA and immune checkpoint inhibitors in the mouse model of melanoma B16 in vivo.Materials and methods. C57BL/6 mice were subcutaneously transplanted with melanoma B16. On days 6 and 9 posttumor transplantation, monoclonal antibodies to PD-1, PD-L1 and programmed cell death 1 ligand 2 (PD-L2), CTLA-4, lymphocyte-activation gene 3 (LAG-3), or CD276 were intravenously injected into mice at a dose of 100 μg/mouse. RhCypA was injected s/c on days 6–10 post-tumor transplantation at a dose of 100 μg/mouse. The therapeutic effects of combined immunotherapy were evaluated by melanoma B16 growth dynamics and the survival of tumor-bearing mice.Results. In combination with anti-CTLA-4 monoclonal antibodies, rhCypA had the most distinct and prolonged synergic anti-tumor effects until day 19 post-immunotherapy, with an increase in animal lifespan of 70 %. When used with anti-LAG-3 monoclonal antibodies, rhCypA exhibited a synergic therapeutic effect by day 12 post-therapy. Combination of rhCypA with anti-PD-L1 or anti-CD276 monoclonal antibodies had short-term synergic effects until day 5 after therapy. Recombinant human CypA impeded the anti-tumor effects of dual anti-PD-1 + anti-LAG-3 therapy.Conclusion. Our findings pointed out that rhCypA could significantly improve therapeutic effects of individual immune checkpoint inhibitors. Therefore, rhCypA could be potentially proposed as a component of combined anti-tumor immunotherapy.